2017
DOI: 10.1007/s12088-017-0694-9
|View full text |Cite
|
Sign up to set email alerts
|

Phage Application for the Protection from Acute Hepatopancreatic Necrosis Disease (AHPND) in Penaeus vannamei

Abstract: Acute hepatopancreatic necrosis disease (AHPND) caused by has been one of the most problematic diseases in marine shrimp aquaculture throughout Southeast Asia and Latin America. To evaluate the effectiveness of a bacteriophage (phage) treatment for AHPND, a series of bioassays were carried out in a marine shrimp () model using an AHPND- strain that is highly pathogenic to shrimp. We monitored the mortality and histopathological changes during phage treatment. Shrimps treated with phage prophylaxis and phage th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 10 publications
2
26
0
1
Order By: Relevance
“…Culot, et al Aquaculture 513 (2019) 734423 In most of published data, timing has proved to be a very important factor regarding phage therapy. Mortality typically increases heavily as treatment time reaches a few hours post infection (Jun et al, 2018;Lomelí-Ortega and Martínez-Díaz, 2014;Martínez-Díaz and Hipólito-Morales, 2013).The best choice seems to administer phages before the infection starts and continue thereafter, as a prophylactic and therapeutic treatment. This need for an early administration might be linked to the time necessary for the phages to reproduce and become sufficiently concentrated in order to make their host's population collapse before the bacterial infection reach an irreversible situation.…”
Section: How To Ideally Use Phages?mentioning
confidence: 99%
“…Culot, et al Aquaculture 513 (2019) 734423 In most of published data, timing has proved to be a very important factor regarding phage therapy. Mortality typically increases heavily as treatment time reaches a few hours post infection (Jun et al, 2018;Lomelí-Ortega and Martínez-Díaz, 2014;Martínez-Díaz and Hipólito-Morales, 2013).The best choice seems to administer phages before the infection starts and continue thereafter, as a prophylactic and therapeutic treatment. This need for an early administration might be linked to the time necessary for the phages to reproduce and become sufficiently concentrated in order to make their host's population collapse before the bacterial infection reach an irreversible situation.…”
Section: How To Ideally Use Phages?mentioning
confidence: 99%
“…For pH stability, 100 μl of phage lysate was mixed with 900 μl of SM buffer in a pH range 2 to 10 and incubated at 30 °C for 1 hour. For temperature stability, 50 μl of phage lysate was incubated for 1 hour at different temperatures; 4,20,25,30,37,40,50,60, and 70 °C. For both tests, phage infectivity was determined by performing a spot test.…”
Section: Methodsmentioning
confidence: 99%
“…In a follow‐up study, Jun et al . () demonstrated that prophylactic and prophylactic/therapeutic treatments (oral or immersion) with pVp‐1 phage protect shrimp (50%–100% survival) against V. parahaemolyticus ‐AHPND lethal challenge.…”
Section: Phages Against Bacteria Causing Ahpndmentioning
confidence: 99%